Anti-inflammatory activity of dominant compound of mahkota dewa fruit Phaleria macrocarpa Scheff. Boerl - Mariani, Ria; Wirasutisna, Komar Ruslan; Nawawi, As’ari; Adnyana, I Ketut (Indonesian Journal of Pharmacy, 2010)
The anti-inflammatory effectof dominant compound of mahkota dewa fruit (Phaleria macrocarpaScheff. Boerl), a hydroxyl benzophenon glucoside,to Wistar  female  rats  (using  λ-karagenan  as  inflammatory  inducer)  has  been investigated.   The inflammation was measured by pletismometer.  The test has been used physiology NaCl solution as a control andNaproxen at a dose of 22.5 mg/kg body weight as a standard. Anti-inflammatorytest was showed that the decreased  inflammation  of  the  isolate  at  a  dose  of  22.5  mg/kg  body  has  twice lower than the standard.Key words:  Phaleria  macrocarpa,  anti-inflammatory  activity,  hydroxyl  benzophenon glucoside